The factors influencing user loyalty in virtual green games: An empirical study based on ant forest - Haodong Wu; Yinying Tao; Manshu Huang (Sustainable Futures, 2025)
As companies ramp up investments in environmental protection, green virtual games such as Ant Forest have gained prominence, making sustained user engagement a critical challenge. This study investigates the factors driving user loyalty in green virtual games by extending the Technology Acceptance Model (TAM) and applying it to Ant Forest. This study extend the TAM framework by integrating corporate social responsibility (CSR), corporate credibility (CC), and corporate image (CI) with achievement (ACH) and social interaction (SI) motivations, to examine how perceived ease of use (PEOU) and perceived usefulness (PU) influence user loyalty. Structural equation modeling analysis of 422 valid responses reveals that all examined constructs—including corporate factors (CSR, CC, CI), user motivations (ACH, SI), and technology acceptance factors (PU, PEOU)—significantly and positively affect user loyalty, with corporate credibility (CC) demonstrating the strongest predictive effect. This study uncovers the intrinsic relationships among CSR, CC, and CI, emphasizing the value of green virtual games in guiding user behavior toward sustainability. It provides a proactive approach for businesses to engage in environmental protection and demonstrates the potential of these games to lead society toward a greener, more sustainable future.